THE EFFECTIVENESS OF ”GRAMMAR BAHASA INGGRIS” APPLICATION IN IMPROVING STUDENTS’ GRAMMAR - Darojatun Qurotu A’yun; Jajat Imanudin (Universitas Islam Al-Ihya Kuningan, 2021)
This study was done to find the effectiveness of Grammar Bahasa Inggris application in improving students’ grammar on simple present tense, which was observed and analyzed from grade ten students in SMK Darul Ulum Kuningan. The method used in this study was quantitative. The researcher took 16 students to be a sample of this study using random sampling. The sampling in this study was two groups consist of eight students for experimental group and eight students for control group. Before giving treatment, the writer gave pre-test. After giving pre-test, students in experimental group are taught by Grammar Bahasa Inggris application and control group without it. Finally, Post-test is given after giving the treatment. Then, it was analyzed by using t- test. The result showed that t-test is higher than t-table, t-test (t0) > t-table (tt) (2,48 > 2,145). It means that Ha is accepted while H0 is rejected is rejected. It can be summarized that there is significant different between students’ grammar using Grammar Bahasa Inggris application and without using Grammar Bahasa Inggris application. The writers concluded that using Grammar Bahasa Inggris is effective to improve students’ grammar specially on simple present.